2016
DOI: 10.1007/s00705-016-2970-0
|View full text |Cite
|
Sign up to set email alerts
|

The entry of cucumber mosaic virus into cucumber xylem is facilitated by co-infection with zucchini yellow mosaic virus

Abstract: We investigated the synergistic effects of co-infection by zucchini yellow mosaic virus (ZYMV) and cucumber mosaic virus (CMV) on viral distribution in the vascular tissues of cucumber. Immunohistochemical observations indicated that ZYMV was present in both the phloem and xylem tissues. ZYMV-RNA was detected in both the xylem wash and guttation fluid of ZYMV-inoculated cucumber. Steam treatment at a stem internode indicated that ZYMV enters the xylem vessels and moves through them but does not cause systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…The systemic transport of PDV seems to occur equally in sieve tubes and xylem vessels, as shown by us in tobacco [ 33 ]. Similar results were observed in natural hosts.…”
Section: Discussionmentioning
confidence: 91%
“…The systemic transport of PDV seems to occur equally in sieve tubes and xylem vessels, as shown by us in tobacco [ 33 ]. Similar results were observed in natural hosts.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, there are no specific studies on the distribution of WMV within different tissues and cells in the plant, but comparing to other potyviruses it was expected to invade more cell types (Kogovsek et al, 2011). As a further complication, the distribution of viruses in mixed and individual infections could be different, as it was shown for instance in combinations of potyvirus and cucumovirus (Ryang et al, 2004;Mochizuki et al, 2016). Interestingly, in sweet potato plants co-infected by SPCSV and potyviruses, crinivirus components were detected outside the phloem, in contrast with its restricted phloem localization in single infections (Nome et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To date, at least 39 plant viruses have been reportedly found in the xylem-associated cells of many different hosts, including herbaceous and perennial woody plants ( Table 1 ). Interestingly, the majority of xylem-invading viruses (35/39) studied to date belong to the group of positive-sense single-stranded RNA (+ssRNA) viruses in the following families: Alphaflexiviridae , Benyviridae , Bromoviridae , Closteroviridae , Potyviridae , Secoviridae , Sobemoviridae , Tombusviridae , and Virgaviridae ( Table 1 ) [ 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Other viruses are three single-stranded DNA (ssDNA) viruses in the family of Geminiviridae [ 37 ] and a negative-sense RNA virus in the family Rhabdoviridae ( Table 1 ) [ 9 ].…”
Section: Examples Of Xylem-invading Virusesmentioning
confidence: 99%
“…In one experiment, a portion of a cucumber stem was steam-treated, followed by inoculation with Zucchini yellow mosaic virus (ZYMV) at a site beneath the treated area. The detection of the virus in the xylem of the upper leaves demonstrated that ZYMV could enter xylem vessels and move [ 6 ]. Stem steam-treatments in other herbaceous host–virus pathosystems, which included Turnip mosaic virus (TuMV) in the Nicotiana benthamiana Domin [ 8 ], and Southern bean mosaic virus (SBMV) in the pinto bean ( Phaseolus vulgaris L.) [ 26 , 28 ], resulted in similar findings.…”
Section: Techniques For Studying Virus Invasion Into the Xylemmentioning
confidence: 99%
See 1 more Smart Citation